Surgical Services in Bangladesh: Glorious 50 years for Bangladesh College of Physicians and Surgeons - Hossain , Md Sanawar (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Abstract not available J Bangladesh Coll Phys Surg 2022; 40: 3